Factors Affecting Rupiah Exchange Rate on US Dollar - Muhamad Faeqi Hadi Saputra; Ht.Suhut, Hazri Wahyuni (Journal of Sustainable Economics, 2025)
This research aims to analyze the influence of interest rates, inflation, and economic growth (GDP) on the rupiah exchange rate on the US dollar. The results of research was analyzed using SPSS Version 25.0. It reveals that the determinant coefficient (R) of 0.6580, which mean the correlation between interest rates, inflation, and economic growth on the rupiah exchange rate for the US dollar is 65,80%. Meanwhile, the R Square value is 0,433, which means that the contribution of the interest rate, inflation, and economic growth variables to the rupiah exchange rate on the US dollar is 43,33% and the rest was influenced by other variables. Considering at each variable, it is known that the interest rate variable has a significant and influential effect on the rupiah exchange rate on the US dollar. The inflation variable has an influence but is not significant on the rupiah exchange rate on the US dollar. Meanwhile, the economic growth variable has an influence and is significant on the rupiah exchange rate on the US dollar. The implication of this research is that the government must concern to interest rates and economic growth in order to increase the rupiah exchange rate on the US dollar.